So ... you're going to college - Ferm, Vergilius Ture Anselm, 1896-1974. (North Quincy, Mass. Christopher Publishing House, 1972)
Advice for the college student on such topics as how to study, choosing courses, making friends, and achieving a philosophy of life.
1
Keywords: Education, Higher -- Handbooks, manuals, etc; College student orientation -- Handbooks, manuals, etc